ANALISIS PERUBAHAN KINERJA DAN STRUKTUR EKONOMI KABUPATEN SIDOARJO SEBELUM DAN SAAT TERJADINYA SEMBURAN LUMPUR LAPINDO - Sutikno, . (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2010)
This study aims to identify patterns of growth and structural change in the economic sector and to analyze the performance of economic sectors and social-economic impact of the â€œLumpur Lapindoâ€ on the area in Sidoarjo. Analyze to identify patterns of growth and contribution to economic sectors and the performance of economic sectors, thus are: Location Qoution, Ratio Analysis of Growth Models, and Analysis Overley. Based on the results of base analysis, the potential and performance the economic sector before and during the â€œLumpur Lapindoâ€ occurred, indicating that the amount of the basic sector and the potential sectors in the District of Porong, Tanggulangin, and Jabon decreased in the event of â€œLumpur Lapindoâ€. Based on the results of analysis of social-economic losses from the Lapindo mudflow, the following results are obtained. Lapindo mudflow incident has caused damage to property in the area around the blast center. Damaged assets consist of: 1) Land and buildings housing residents; 2) productive plants such as rice, sugarcane, and pulses; 3) Buildings and equipment; 4) infrastructure such as toll roads, electricity networks, irrigation networks, water network, telecommunications networks, gas pipelines, with total losses estimated at Rp 33.27 trillion.